Residential Satisfaction of Public Housing Dwellers in Alkish and Alzaiton, Benghazi City, Libya - Mohamed Athram, Huda (2000)
One of the major concerns of the Libyan Government is to provide adequate housing for its citizens. The state holds an important social responsibility of fulfilling the needs for housing especially for the lower income group. Previous studies have shown that inadequate space is one of the problems faced by low income dwellers. The shortage of space has affected their daily activities and reduced their housing satisfaction. The main objective of this study was to compare residential satisfaction of public housing in Benghazi City, Libya. The specific objectives were to identify the socio economic background of the respondents to examine the current housing conditions and types of space available to identify the residential satisfaction of the respondents; to identify the aspiration of respondents towards their housing to examine the renovation that have been made on the houses and to determine the significant factors that contribute to residential satisfaction. A total of one hundred and sixty-four low income households from two types of houses namely, single storey terrace houses and flats in Alkish and Alziton areas were randomly selected and interviewed using questionnaires in this study. Three hypotheses were tested. The T -test was used to determine the significant difference between types of house and residential satisfaction, and to determine the significant difference between respondents who built and did not build additional bedrooms and residential satisfaction. Logistic regression and multiple regression analysis were used to determine the significant variables that contributed to residential satisfaction. The results of the study showed that the households were from low income groups, with large household size and were at an expanding stage of their family life cycle. Most of the households experienced room deficits. In terms of residential satisfaction, the services available received the highest level of satisfaction followed by facilities and housing unit. As .for the evaluation of the residential satisfaction the Yeh index of satisfaction (YIS) was used. There were twenty seven items in the Yeh index which received positive index while the remaining nine items had negative index. Results also revealed that the respondents who lived in terrace houses were satisfied with thirty two of the items and were dissatisfied with four items. The respondents living in flats were satisfied with twenty' four of the items and dissatisfied with twelve items. The Yeh index confirmed that the dwelling unit was the major source of dissatisfaction. The results also showed that there was a tendency for the terrace house dwellers to improve their house when their income permitted, which helped to reduce the space deficit. The T-test indicated a significant difference between types of housing and residential satisfaction which implied that those who stayed in terrace houses were more satisfied with their dwelling. The T-test also indicated there was a significant difference between respondents who added bedroom and those who did not, with regards to residential satisfaction. When Logistic regression analysis (logistic model) is used, it is found that the significant variables that contributed to the residential satisfaction were bedroom deficit followed by respondents plan to move. It is also found that when multiple regression analysis (non-logistic model) is used the significantly contributed variables were bedroom deficit, plan to move and age of eldest child. The results of this study revealed certain factors that can cause households to be dissatisfied with their houses. Thus, housing planners should take into consideration those characteristics identified in their housing planning and implementation. Alternative future housing designs should help to reduce space deficit especially among those households who had no other choice but to stay in their present house.